Organic Compounds in a Sub‐Antarctic Ice Core: A Potential Suite of Sea Ice Markers. Issue 16 (27th August 2019) - King, A. C. F.; Thomas, E. R.; Pedro, J. B.; Markle, B.; Potocki, M.; Jackson, S. L.; Wolff, E.; Kalberer, M.
Abstract: Investigation of organic compounds in ice cores can potentially unlock a wealth of new information in these climate archives. We present results from the first ever ice core drilled on sub‐Antarctic island Bouvet, representing a climatologically important but understudied region. We analyze a suite of novel and more familiar organic compounds in the ice core, alongside commonly measured ions. Methanesulfonic acid shows a significant, positive correlation to winter sea ice concentration, as does a fatty acid compound, oleic acid. Both may be sourced from spring phytoplankton blooms, which are larger following greater sea ice extent in the preceding winter. Oxalate, formate, and acetate are positively correlated to sea ice concentration in summer, but sources of these require further investigation. This study demonstrates the potential application of organic compounds from the marine biosphere in generating multiproxy sea ice records, which is critical in improving our understanding of past sea ice changes. Plain Language Summary: Ice cores are vertical cylinders of ice drilled from an ice sheet, younger at the top and older at the bottom. Particles emitted from plants and animals on land and in the ocean, containing organic chemical compounds, are carried by atmospheric circulation, deposited on the ice surface, and become trapped inside ice layers. They are a record of environmental conditions at the location and time the particles originally formed. Here, we look for a number of these organic compounds in an ice core from Bouvet Island in the sub‐Antarctic. We find the amounts of some are related to amounts of sea ice around the island in the spring. This is because the particles are originally emitted by phytoplankton, for which the amount of sea ice that year controls the amount of phytoplankton (more sea ice in the winter = greater area of sea ice break up in spring = more phytoplankton in spring). We find other organic compounds are related to amounts of sea ice in summer, but their sources are less well known. Combining these records with their relationships to sea ice will be useful in helping us to better understand sea ice changes in the past. Key Points: We analyzed a suite of organic compounds, alongside commonly measured ions, in the first ever shallow ice core from Bouvet Island Multiple marine‐sourced organic compounds are detected throughout the core Organic compounds, alongside MSA, show significant positive correlations with sea ice